2022
DOI: 10.1186/s40246-022-00384-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of m6A methylation in osteosarcoma biological processes and its potential clinical value

Abstract: Osteosarcoma (OS) is the most common primary malignant bone tumor in children and young adults and has a poor prognosis. Recent developments in the field of high-throughput sequencing technology, particularly in methylated RNA immunoprecipitation sequencing (MeRIP-seq), have led to renewed interest in RNA methylation. Among the various RNA modifications, N6-methyladenosine (m6A) modifications are the most common. Emerging evidence suggests that m6A methylation can affect the complexity of cancer progression by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…Numerous signal pathways mediated by m 6 A are associated with human tumor prognosis. Besides, m 6 A can modulates the expression of transcripts to mediate the target in signalling pathway, leading to methylation change by different m 6 A-correlated enzymes (Wu et al,, 2022). YTHDF3 is a canonical m 6 A reader in the tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous signal pathways mediated by m 6 A are associated with human tumor prognosis. Besides, m 6 A can modulates the expression of transcripts to mediate the target in signalling pathway, leading to methylation change by different m 6 A-correlated enzymes (Wu et al,, 2022). YTHDF3 is a canonical m 6 A reader in the tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…N 6 -methyladenosine (m 6 A) acts as the most abundant and common mRNA's modi cation, which plays crucial roles and functions in series of biological processes (Dang et al,, 2021, Fang et al,, 2021. The effects of m 6 A on mRNA methylation and its biological functions in osteosarcoma are of great signi cance (Wu et al,, 2022, Zhang et al,, 2021b. For example, m 6 A writer WTAP (Wilms' tumor 1 associated protein) enhanced the stability of FOXD2-AS1 transcripts to promote the methylation modi cation and accelerate the osteosarcoma progression through FOXD2-AS1/m 6 A/FOXM1 complex manner (Ren et al,, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The specific implications of RNA methylation modifications in osteosarcoma have also been increasingly studied in recent years. Numerous investigations have revealed that methylation modifications extensively regulate osteosarcoma proliferation, apoptosis, migration, invasion, and tumor microenvironment [30] , [31] , [32] . Furthermore, aberrant expression of methylation modification regulators is intimately correlated with poor prognosis and chemotherapy resistance in osteosarcoma [30] , [33] .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is an extreme lack of studies on the correlation between lncRNAs and the slow ow/no re ow phenomenon in STEMI patients, and even fewer studies have discussed the expression of lncRNAs in coronary blood in the presence of slow ow/no re ow, so we believe that lncRNAs and the slow ow/no re ow phenomenon in myocardial ischemia reperfusion injury still need further investigation. N6-methyladenosine (m6A) modi cation is one of the common epigenetic modi cations, accounting for more than 80% of all RNA modi cations [13]. Previous studies have found that m6A methylation is widely involved in the development of various types of cardiovascular diseases [14] and may provide a reference to explore the occurrence of slow ow/no re ow.…”
Section: Introductionmentioning
confidence: 99%